1994
DOI: 10.1182/blood.v84.12.4234.bloodjournal84124234
|View full text |Cite
|
Sign up to set email alerts
|

A defect in the early phase of T-cell receptor-mediated T-cell activation in patients with common variable immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is characterized by an impairment of specific antibody production and a decrease in all or selected Ig isotypes. Abnormalities at the level of the B cells, T cells, and antigen-presenting cells have been described. In the present study, we have focused our attention on T-cell activation in CVID. T cells from 15 of 24 patients failed to respond to recall antigens (eg, tetanus toxoid, Escherichia coli). Of these 15 patients, 11 were studied in detail and showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(33 citation statements)
references
References 29 publications
2
30
1
Order By: Relevance
“…There is much evidence for a reduction in IL-2 production in CVID. This comes from mitogenic studies measuring DNA synthesis, IL-2 mRNA and IL-2 secreted [4][5][6]13,14]. However, we now show with the directly conjugated anti-IL-2 antibody that there is no difference between CVID and normals in the mean proportion of CD4 + or CD8 + cells making IL-2.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…There is much evidence for a reduction in IL-2 production in CVID. This comes from mitogenic studies measuring DNA synthesis, IL-2 mRNA and IL-2 secreted [4][5][6]13,14]. However, we now show with the directly conjugated anti-IL-2 antibody that there is no difference between CVID and normals in the mean proportion of CD4 + or CD8 + cells making IL-2.…”
Section: Discussionmentioning
confidence: 72%
“…Since we and others have reported that some CVID patients have subnormal DNA synthesis in response to PHA [4], we compared PHA with PMA and ionomycin for the kinetic induction of IL-2, IFNand TNF-in normal cells. PHA was far less effective than PMA and ionomycin and no significant cytokine 520 expression was seen in normal CD4 + cells for up to 14 h of stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying an experimental system free of APC, stimulation of the TCR in combination with distinct costimulatory molecules enabled us to analyse further the nature of the defect. Previous studies reported defective T cell responses to recall antigens in patients with CVID [8][9][10]34,35], and in a recent study impaired antigen response was attributed to a , CD40L expression in this cell population. A marker (Ml) was set to identify the percentage of CD40L' cells.…”
Section: T Cell Help For B Cells Is Impaired In Cvid Patientsmentioning
confidence: 76%
“…In this regard, 15 years ago, work demonstrated a decreased Ca ++ signal in T cells of some CVID patients. 58 And recently, a strong correlation between decreased BCR-induced Ca ++ signaling and CVID patients with low percentage of smB cells, but expansion of CD21 low B cells (Freiburg classification group Ia; Ref. 3), endorsed the classification and demonstrated a cell-intrinsic activation defect in B cells of these patients.…”
Section: The First Dimension-the Genetic Levelmentioning
confidence: 99%